Haloperidol Use in the Emergency Department for Gastrointestinal Symptoms: Nausea, Vomiting, and Abdominal Pain. Issue 6 (1st June 2021) - Shahsavari, Dariush; Reznick-Lipina, Kaitlin; Malik, Zubair; Weiner, Mark; Jehangir, Asad; Repanshek, Zachary D.; Parkman, Henry P.
Abstract : INTRODUCTION: Haloperidol (HL) has successfully been used for nausea and abdominal pain in emergency departments (EDs). This study examines outcomes and predictive factors for clinical improvement of patients presenting to an ED with gastrointestinal (GI) symptoms (nausea, vomiting, and abdominal pain) who received HL. METHODS: Review of patients' records who presented to our ED between August 2016 and March 2019 with GI symptoms and received HL. International Classification of Diseases, Tenth Revision codes were used to identify patients. RESULTS: In all, 281 patients (410 encounters) presented to the ED with GI symptoms and received HL for their symptoms: 66% were women, 32% had diabetes, 68% used marijuana, and 27% used chronic opioids. Patients received HL 1.1 ± 0.3 times with dose 2.5 ± 3.0 mg, mostly intravenously (84.6%). Total ED length of stay was 7.5 ± 3.9 hours (3.2 ± 2.1 hours before HL and 4.4 ± 3.4 hours after). Approximately 4.4% of patients developed side effects to HL, including 2 patients with dystonia which improved with medication before discharge. Most patients (56.6%) were discharged home while 43.2% were admitted to hospital mostly because of refractory nausea or vomiting (70.1%). Receiving HL as the only medication in the ED led to lower hospital admission (odds ratio = 0.25, P < 0.05). Diabetes, cannabinoid use, anxiety, male sex, and longer ED stay were associated with increased hospital admissions. DISCUSSION: Most patients treated in our ED with HL for GI symptoms, particularly nausea, vomiting, and/or abdominal pain, were successfully treated and discharged home. HL use seemed relatively safe and, when used as the only medication, led to less frequent hospital admissions.